Pelaksanaan Pengawasan Terhadap Alat Penangkapan Ikan Pukan Pukat Hela (Trawls) Di Kecamatan Selayar Kabupaten Lingga - Mardiana Mardiana; Agus Hendrayady; Ramadhani Setiawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Implementation of Supervision of Trawl Fishing Equipment (Trawls) in Selayar District, the use of these trawls which are still operating due to supervision that is not running effectively. This study aims to determine the Implementation of Supervision of Trawling Equipment in Selayar District, Lingga Regency. The research method used is a qualitative research approach with data collection techniques, namely interviews, observation, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. In this study using the theory of supervision according to Joko Widodo (2016: 94). The results of this study indicate that: a. the supervisors implementing the policy, the supervisors, namely the agencies and other auxiliary apparatus in this supervision are still not running well or have not been implemented because there are still fishermen who use the Trawl fishing gear, b. Standard Operating Procedures (SOP), under supervision have been implemented in carrying out supervision, so for this indicator it has been implemented sufficiently and is running according to the specified SOP, c. Financial Resources and Equipment, in this indicator there is still a lack of budget and some equipment is under supervision, so for this indicator it is still not sufficiently implemented because it is still constrained by a lack of budget, d. Schedule for Supervision Implementation, for the schedule itself, of course there is a special schedule but for carrying out self-monitoring sometimes it doesn't necessarily depend on the incoming reports, for this indicator it has also been implemented because the existing schedule is also in accordance with the time and reports received. Based on the research indicators, it can be concluded that the implementation of this supervision has not run optimally because there are still many fishermen in the Selayar District who use trawls. The recommendation that is needed is the implementation of supervision that should be carried out effectively so that there is no longer use of trawl fishing gear in Selayar District.